PENTRAXIN LEVELS AS PREDICTORS OF CARDIOVASCULAR RISK IN TYPE 2 DIABETES MELLITUS - VYSHNAVI MS,; ARUL SENGHOR KA,; VINODHINI VM,; RENUKA P,; KUMAR JS, (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: Pentraxin-3 (PTX3) is an acute phase protein, considered as a vascular proinflammatory reflector, and its link with dyslipidemia environment and oxidative stress truths the risk of cardiovascular disease. This study evaluates the association of PTX3 and atherogenic markers (total cholesterol [TC]/high-density lipoprotein [HDLc], low-density lipoprotein [LDLc]/HDLc, triglycerides [TGL]/HDLc, non-HDLc, atherogenic coefficient) in normoalbuminuric micro and macroalbuminuria diabetic individuals. Methods: The analytical observational research work included 86 participants with a duration of diabetes mellitus <5 years without complications. Participants were grouped based on glycated hemoglobin and urine albumin creatinine ratio as normoalbuminuric, micro, and macroalbuminuria. Lipid profile analytes were measured in the Beckman Coulter AU series and PTX3 was analyzed using a standard kit. The atherogenic coefficient is the ratio between non-HDLc and HDLc that epitomizes cardiovascular risk. Results: Elevated PTX3 values in poor glycemic diabetic individuals with albuminuria patient. PTX3 results statistically correlated positively with TC/HDLc, TGL/HDLc, non-HDLc/HDLc (atherogenic coefficient), and non-HDLc. These findings strengthen the potential link between PTX3 and atherogenic risk in diabetic patients with poor glycemic status. The receiver’s operative characteristics curve supported PTX3 cut-off of 2.49 ng/mL, the area under the curve was 0.739 with a diagnostic sensitivity of 79.1% and specificity of 72.1%, with a significant p value. Conclusion: PTX3 is considered a promising marker of the inflammatory environment due to poor glycemic and lipidemic environment, thereby relating to the likelihood of complications in diabetes. This study substantiates that PTX3 is a valuable marker for assessing early cardiovascular risk and emphasizes the importance of lifestyle modification and therapeutic intervention.